The toxicity of angiotensin converting enzyme inhibitors to larvae of the disease vectors Aedes aegypti and Anopheles gambiae - Abu Hasan Z.-I.; Williams H.; Ismail N.M.; Othman H.; Cozier G.E.; Acharya K.R.; Isaac E.R. (Nature Publishing Group, 2024)
Indexed by WOS/SCOPUS/ERA